2017
DOI: 10.1073/pnas.1708492114
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of synaptic protein membrane fusion interfaces

Abstract: Neurotransmitter release is orchestrated by synaptic proteins, such as SNAREs, synaptotagmin, and complexin, but the molecular mechanisms remain unclear. We visualized functionally active synaptic proteins reconstituted into proteoliposomes and their interactions in a native membrane environment by electron cryotomography with a Volta phase plate for improved resolvability. The images revealed individual synaptic proteins and synaptic protein complex densities at prefusion contact sites between membranes. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 38 publications
7
64
0
Order By: Relevance
“…5d). Consistent with this model of the primed state, constitutive insertion of Cpx into the SNARE complex locks release 42 , and inclusion of Cpx increases the separation between membranes in a reconstituted system as observed by electron cryo-tomography 43 .…”
Section: Discussionsupporting
confidence: 62%
“…5d). Consistent with this model of the primed state, constitutive insertion of Cpx into the SNARE complex locks release 42 , and inclusion of Cpx increases the separation between membranes in a reconstituted system as observed by electron cryo-tomography 43 .…”
Section: Discussionsupporting
confidence: 62%
“…In such cases, there will be no inner Syt ring or Syt buttress to the SV to clamp the SNAREpins, so fusion will follow constitutively. This extension of our hypothesis suggests that each constitutive fusion event will involve only a handful of SNARE complexes and associated stoichiometric MUN‐containing chaperones as recently found by super‐resolution imaging of constitutive fusion at the PM 70.…”
Section: Other Variations On the Buttressed‐ring Hypothesissupporting
confidence: 68%
“…Electron cryo-tomography studies revealed that nearly all associated SV-PM vesicle pairs fused upon Ca 2+ -addition within 1 min (Gipson et al, 2017). Moreover, the lack of C1C2BMUN fragments at a considerable number of contact sites before Ca 2+ addition is consistent with the notion that Munc13 catalyzed proper SNARE complex assembly and then dissociated from some of the primed pre-fusion complexes, prior to Ca 2+ triggering.…”
Section: Discussionmentioning
confidence: 99%